Company pensions and taxation - Daniel Besendorfer; A. Katharina Greulich (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2001)
This article deals with the conditions for profitability of company pensions, comparing the in fluence of immediate and deferred taxation under different rules of funding the pension contributions. The model provides a systematic general framework to investigate incentive compatibility of such pension schemes in most western countries. The implications of real world complications such as multiple interest rates and progressive income taxation are also considered. The findings suggest that although it might be helpful to discriminate company pension contracts against other forms of private old age securities for the improvement of this special contract itself, one has to evaluate carefully the impact on effciency in the overall economy.
Keywords: H25; J33; 330; Betriebliche Altersversorgung; Steuer; Theorie der Unternehmung; Steuerwirkung; Theorie